2016
DOI: 10.1016/j.pmedr.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime cigarette smoking is associated with abdominal obesity in a community-based sample of Japanese men: The Shiga Epidemiological Study of Subclinical Atherosclerosis (SESSA)

Abstract: Studies from Western countries suggest that smokers tend to display greater abdominal obesity than non-smokers, despite showing lower weight. Whether this holds true in a leaner population requires clarification. Using indices of abdominal obesity including visceral adipose tissue, we examined whether lifetime cigarette smoking is associated with unfavorable fat distribution among Japanese men.From 2006 to 2008, we conducted a cross-sectional investigation of a community-based sample of Japanese men at 40–64 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…We have already reported that smoking status is cross-sectionally associated with a greater degree of abdominal obesity. 37 We assume that the same mechanism could explain the association between PFV and smoking. In addition, a significant association between smoking status and resting heart rate was noted by Linneberg et al 38 We suggest that smoking and increasing resting heart rate might contribute (at least in part) to the risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported that smoking status is cross-sectionally associated with a greater degree of abdominal obesity. 37 We assume that the same mechanism could explain the association between PFV and smoking. In addition, a significant association between smoking status and resting heart rate was noted by Linneberg et al 38 We suggest that smoking and increasing resting heart rate might contribute (at least in part) to the risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In aggregate, data from these studies suggest that smoking is associated with deleterious changes in body composition, despite being linked to reduced body weight [25]. Individuals who smoked >20 cigarettes per day had an adjusted odds ratio for abdominal obesity of 1.93 (95% CI: 1.16 to 3.21) as compared to never-smokers [26].…”
Section: Cigarette Smoking Impacts Body Weight and Composition Peripmentioning
confidence: 99%
“…Cross-sectional data from 21,828 men and women aged 45 to 79 years in the United Kingdom demonstrated that smokers had higher waist-to-hip ratios as compared to non-smokers, and this measure was directly correlated with the amount of smoking [27]. Furthermore, in a cross-sectional study of 513 Japanese men, greater lifetime smoking exhibited a significant and positive association with higher waist-to-hip ratio and the visceral adipose to subcutaneous adipose ratio, assessed by computerized tomography (CT) scans [25]. These findings support the general notion that smoking is linked to adverse fat distribution.…”
Section: Cigarette Smoking Impacts Body Weight and Composition Peripmentioning
confidence: 99%
“…The Shiga Epidemiological Study of Subclinical Atherosclerosis (SESSA) is a population-based study which recruited 40-to 79-year-old men, randomly selected in 2006-2008 (baseline), from the general population in Kusatsu City, Shiga, Japan (participation rate of 46%). [19][20][21] Although SESSA is an observational cohort study with follow-up in 2010-2014, our present analysis only involves data from the follow-up because CASI score was not measured at baseline. A total of 853 men participated in the follow-up, a participation rate of 78% (see eFigure 1 for selection flow).…”
Section: Study Participantsmentioning
confidence: 99%